APLIKASI KAMUS BAHASA LATIN HEWAN DAN TUMBUHAN MENGGUNAKAN METODE BRUTE FORCE DAN FITUR AUTOCOMPLETE BERBASIS ANDROID - Nur Imran Ruslan; Bambang Pramono; Subardin Subardin (Informatics Engineering Department of Halu Oleo University, 2016)
Latin dictionary of animals and plants is a development of Android-based mobile application that allows users to search for words easily and quickly. This application allows users to quickly search for the meaning of the Latin animals and plants. The process that occurs in these applications include word similarity search using the search Brute Force. Input form Animal or Plant name is a string value that will be used as search parameters in the database. The test results Dictionary search using the Brute Force successfully at speeds of less than one second search time. In this test, is used six times a search in which three of the six search using the Animal and Plant remainder using the word. Speed search process using Brute Force methods depend on the length of the word or (String) sought. Keywords— Android Dictionary, Dictionary of Animals and Plants, Brute Force